The Ecological Approach To The Study of Medan Belawan Sub District - Rara Ayu Rati Kumala Dewi (International Journal of Architecture and Urbanism, 2020)
The ecological approach is the study of the spatial and temporal relations of human beings as affected by the selective, distributive, and accommodative forces of the environment. This condition also stimulates industrial growth, both large, medium, small, and the housing industry. In 2019, it was noted that there were 28 large medium industries, 150 small industries, and 73 home industries. Industrial growth has stimulated the growth of settlements in this region where the growth of the settlements follows the growth of the industry itself. This has caused the area around the industry to have transformed into a densely populated area. The results of the study show that Medan Belawan Sub-District is an area that grows, and its development is influenced by the coast.